Customary Village Authority in Coastal Area Management : an Ius Constituendum Perspective - Widnyana, I Made Adi (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 12 No 2 (2023)DO - 10.24843/JMHU.2023.v12.i02.p06, 2023)
The research was aimed to examine the authority of Adat village in the management of coastal areas based on Bali Province Regional Regulation No. 4 of 2019 concerning Adat Village and constructing the regulation on forest park in coastal areas from the perspective of ius constituendum. This was normative legal research using statutory approach and conceptual approach. The study indicated that there is a conflict of norm in the authority to manage the coastal areas in Bali, which according to the Article 25 point 1 c and d of the Perda Desa Adat , it can be seen that Adat Village has the authority to manage the coastal areas, which includes Tahura Ngurah Rai, however, according to Article 1 point 10 of the Regulation of the Minister of Environment and Forestry No: P.10/Menhut-II/2009, the authority to manage the forest park is delegated to the UPTD Tahura Ngurah Rai, which was formed and is under the Bali Provincial Environment and Forestry Services as the holder of autonomous forest management rights in Bali. Hence, it is important to harmonize the application of the authority of Adat Village with the national regulation to avoid conflict of norms by taking in to account the Stufenbau Theory and the principles of lex superior derogat legi inferiori in reforming a regulation on forest park in coastal area in the future as ius constituendum